The Circular Economy and Circular Building Practices in Luxembourg - Paula Hild (Circular Economy and Sustainability, 2023)
This article analyses the circular economy in Luxembourg using a retroductive approach to the study of practices. It presents the circular economy vision in Luxembourg as a governmental concept since 2015 that operationalises mainly within the building sector. Based on 66 semi-structured interviews with key stakeholders, the article expands on what circularity means for architects, engineers, and building firms. In this sense, the building sector in Luxembourg deals with three main topics: (a) circular design concepts, (b) circular materials management (i.e. materials passport), and (c) digitisation. The article discusses construction as a bundle of activities that constitutes shared meanings, materials, and competence. The findings illustrate that the circular economy foci in the literature and Luxembourg are path-dependent and mirror the European and national history of sustainability concepts in construction. If and how the circular economy and circular practices contribute to sustainable development in the country still needs consideration and monitoring.
Keywords: 330; Circular economy; Circularity; Building sector; Materials management; Design concepts; Luxembourg